DAMPAK IMBALAN KERJA DAN HARGA POKOK PRODUKSI TERHADAP LABA BRUTO PT. UNILEVER INDONESIA, TBK. - francisca sestri goestjahjanti (Business Management Journal, 2020)
ABSTRACTThe growth of large-scale and medium-scale manufacturing industries in Indonesia today is not yet encouraging and tends to slow down year on year in the first quarter of 2019 and in the 2018 quarter, become down 0.80 percent, due to political temperatures heating up ahead of the presidential election. The rejection of the Omnibus Law made the Company to recalculate the determination of employee benefits which would affect company profits. This study aims to analyze the magnitude of the impact between employee benefits and the cost of good manufacture to the gross profit of PT. Unilever Indonesia, Tbk.. Hypothesis test of this study becomes a reference in establishing the research method. By measuring the dependency between the influencing variables on the affected variable described the mind frame of the model. The analysis technique uses linear regression with the SPSS statistical program. The results of the study are: There is a significant impact between employee benefits on gross profit of 84.90 percent. There is a significant impact between cost of good manufacture on gross profit of 98.70 percent. And simultaneously there is a very significant impact of 99.10 percent between employee benefits and the cost of good manufacture to the gross profit of PT. Unilever Indonesia, Tbk.Keywords:  Employee Benefits, Cost of Good Manufacture, and Gross Profit